Application of Cryogenic Technologies in Deformation Processing of Metals - I.E. Volokitina, A.I. Denissova, A.V. Volokitin, T.D. Fedorova, and D.N. Lavrinuk (Успехи физики металлов, 2024)
The publications in the field of cryogenic-technologies’ applications in the processes of the thermal and deformation treatments of metals are reviewed. The most effective fields of the applications of cryogenic liquids and gases for the heat treatment of working tools and metals (titanium, aluminium, and copper alloys) are in the rolling production and heavy engineering in order to improve the product quality, equipment and tool durability, to reduce the impact on the environment and operating personnel. The effects of cryogenic treatment and cooling on the tool life, wear, cutting temperature, surface roughness, dimensional accuracy, and cutting force are considered. As a result, the use of cryogenic processing and cryogenic cooling in machining processes increases the tool life and improves surface roughness as well as reduces the temperature of the machined surface, energy consumption during operation, and, thus, reduces tool wear that contributes to an increase in productivity. The possibility of obtaining and changing the nanostructure of a metal through the cryogenic cooling is also considered. The topic may be of interest for researchers and scientists in the field of metallurgy, materials science, and nanotechnologies.